The European Union and the Territorial Scope of European Territories - Ziller, Jacques (Victoria University of Wellington Law Review, 2007)
In this paper Professor Ziller addresses the intriguing question of the relationship of the European Union – which is not a state and which has no territory of its own – to the territories of EU Member States. The paper provides a survey of the overseas territories affected and the evolution of the case law of the European Court of Justice on the extent to which the provisions of the EC Treaty apply to the European territories overseas.